Urbanization and Economic Development: A Tale of Two Barriers - Eric Bond; Raymond G. Riezman; Ping Wang (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper we determine the main driving forces underlying the structural transformation and urbanization process in rapidly industrializing countries. We use a dynamic, small open economy model with an abundant supply of surplus labor in rural areas, two types of traded goods manufactured in urban areas, and barriers to both trade and migration. The model is supplemented with quantitative analysis fitting the data from China, to explore the role that reductions in trade and migration barriers played in China's growth and urbanization. We find that the primary drivers for real per capita GDP growth are migration cost reduction and skill accumulation. While trade liberalization is important for urbanization during the transition toward China's admission to the WTO it does not contribute much to real per capita GDP growth. During this transition process, migration cost reduction and TFP changes are also important, accounting for a significant proportion of increased urbanization.
Keywords: O41; O11; F16; R23; 330; barriers to migration and trade; urbanization; economic development; surplus labor